2022
DOI: 10.1177/14614448221075759
|View full text |Cite
|
Sign up to set email alerts
|

Conspiracy theories in online environments: An interdisciplinary literature review and agenda for future research

Abstract: Research on conspiracy theories in digital media has grown considerably in recent years. As a result, the field of research has become more multidisciplinary and diverse. To bridge disciplinary boundaries, identify foci of analysis and research gaps, this study provides an interdisciplinary systematic literature review (2007–2020), analyzing current research on conspiracy theorizing online, both quantitatively and qualitatively. Findings show that the majority of studies lack a definition of conspiracy theorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 45 publications
2
50
0
4
Order By: Relevance
“…The rapidly developed digital environment is considered to have fuelled the amplification and dissemination of conspiracy theories, including those that are GMOs related (Mahl et al, 2022), especially since it gives the public a greater voice and the possibility of becoming communicators based on the empowerment of the digital media environment (Hussein et al, 2020;Mahl et al, 2022). When the growth of the public's scientific literacy cannot keep up with the growth of their voice power in the digital age, Xu and Lu (2019) found that conspiracy theories about GMOs are more likely to appear on the Chinese Internet.…”
Section: Genetically Modified Organism Conspiracy Theories In Chinamentioning
confidence: 99%
“…The rapidly developed digital environment is considered to have fuelled the amplification and dissemination of conspiracy theories, including those that are GMOs related (Mahl et al, 2022), especially since it gives the public a greater voice and the possibility of becoming communicators based on the empowerment of the digital media environment (Hussein et al, 2020;Mahl et al, 2022). When the growth of the public's scientific literacy cannot keep up with the growth of their voice power in the digital age, Xu and Lu (2019) found that conspiracy theories about GMOs are more likely to appear on the Chinese Internet.…”
Section: Genetically Modified Organism Conspiracy Theories In Chinamentioning
confidence: 99%
“…Many conspiracy theories are conceptually ambivalent and analytically complicated. First, even though existing definitions share conceptual elements for understanding conspiracy theories, a comprehensive and consistent framework on how to operationalise ‘conspiracy theories’ is still lacking ( Mahl et al, 2022 ). Second, conspiracy narratives are notoriously diverse and intertwined simultaneously.…”
Section: New Dynamics Of Conspiracy Theories Onlinementioning
confidence: 99%
“…Despite the rapidly growing research interest, scholarship can clearly benefit from further diversification and from integrating more heterogeneous research perspectives. A recent systematic review by Mahl and colleagues (2022) demonstrates that, on the level of geo-location and language, prior studies of conspiracy theories online strongly focused on Western democracies and Anglophone content, neglecting non-Western countries, the Global South and countries in which English is not the dominant language. Regarding the analysed platforms, Mahl and colleagues (2022) demonstrate that studies of conspiracy theories on digital media focus predominantly on major Silicon Valley platforms such as Twitter, Facebook and YouTube and not, for example, on non-Western platforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Don't Look Up tells the story of a team of scientists whose research on a deadly comet approaching Earth is ignored by significant parts of the general population and undermined by the ambitions of politicians -specifically those of the conservative US President Janie Orlean. The film shows several more facets of contemporary challenges to scientific expertise beyond science denial, hostility against scientists, and partisan reasoning, for example conspiracy theories on social media [Mahl, Schäfer & Zeng, 2022], corporate counter-research [Oreskes & Conway, 2010], and populist anti-elitism [Mede & Schäfer, 2020]. Don't Look Up thus offers a vivid picture of current anti-science resentment, the societal settings surrounding it, and ways in which scientists and science communicators can -or cannot -respond to it.…”
Section: Introductionmentioning
confidence: 99%